AN ERROR ANALYSIS IN USING SIMPLE PRESENT TENSE IN DESCRIPTIVE WRITING AT SMAN 1 SUMBER MARGA TELANG, BANYUASIN - Dina Agustina; Renny Kurnia Sari; Hariana Amalia (IKIP Siliwangi, 2024)
This study aimed to identify the types of errors and the most frequent errors in the use of simple present tense in descriptive writing at SMAN 1 Sumber Marga Telang, Banyuasin. This study used the quantitative method. The subjects of this study were X MIPA 1 class students were selected by using the convenience sampling technique. The data were collected using writing task. The data were analyzed and classified based on the taxonomy of surface strategies proposed by Dulay, Burt, and Krashen (1982). The results showed that there were four types of errors: the most frequent error was omission, which indicated that students' difficulty in understanding the use of to be and suffixes s/es in the simple present tense. The frequency of omission errors was 51.72%, followed by misformation errors (18.39%), misordering errors (16.09%), and addition errors (13.79%). Finally, based on the results of this research, the percentage of errors made by students in class X MIPA 1 SMAN 1 Sumber Marga Telang, is still quite high.